Occurrence of Acanthamoeba in hospitals: a literature review - Bullé, Danielly Joani; Benittez, Lisianne Brittes; ROTT, MARILISE BRITTES (Revista de Epidemiologia e Controle de Infecção, 2020)
Acanthamoeba are among the most prevalent environmental protozoans and have a cosmopolitan distribution. The main concern for public health purposes is that they can also be isolated from contact lenses, storage cases and cleaning solutions, ventilation and air conditioning systems, dental treatment units, dialysis units, emergency showers and eyewash stations. These genera include a diversity of pathogenic microorganisms that leads to infectious diseases inside the hospital environment, and it is of the utmost importance to carry out the surveillance, considering mainly the immunocompromised patients, which are more susceptible to these diseases. The level of human health risk and its associations in the hospital environment is unknown, and part of this problem is potentially the lack of correlation between protozoan exposure and symptom onset, which each patient can develop at different periods in time. Studies on the ecology and distribution of non-enteric pathogens in the hospital environment are necessary to understand their potential threat to human health. Thus, this review presents a current overview of the presence of Acanthamoeba spp. in hospital environments aiming to verify their presence in these environments, and look for effective ways to control their presence through disinfection and monitoring measures.